Translation of Reflective Thinking Questionnaire: A Structural Equation Model - Laras Firdaus; Masiah Masiah; Ibrohim Ibrohim; Sri Rahayu Lestari; Ika Nurani Dewi; Alwan Mahsul; Agus Muliadi (Jurnal Penelitian Pendidikan IPA, 2021)
The purpose of this study is to translate, validate the reflective thinking questionnaire, and to explain the reflective thinking profile of UIN Mataram biology prospective teachers. A total 243 of UIN Mataram biology prospective teacher as voluntary respondents. The data analysis process was carried out using the JASP for windows analysis package. Structural equation model testing based on P-value, CFI, and RMSEA. The results of the confirmatory factor analysis, from 16 items were analyzed, only 11 items supported a fit model, with P-value= 0.225, CFI= 0.986, and RMSEA= 0.026. The 11 items reflect four categories of RT (understanding, reflection, habitual action, and critical reflection), show high internal consistency, and show good construct validity. The translation of the RT questionnaire was declared valid and could be used to measure RT.